2021
DOI: 10.7759/cureus.15153
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Immune Thrombocytopenia Associated With Asymptomatic COVID-19 Successfully Managed With Intravenous Immunoglobulin and Glucocorticoids

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease characterized by low platelet counts of <100 × 10 9 /L with the absence of other blood count abnormalities. Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 which is manifested by a severe multisystemic disease. We present the case of a 76-year-old female who presented with ITP associated with COVID-19 and successfully managed with intravenous immunoglobulin and glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This study included a total of 7 case reports, two of them were reported from the United States [ 17 , 18 ], one from Canada [ 19 ], one from Italy [ 20 ], one from Turkey [ 21 ], and one from Greece [ 22 ]. The lowest platelet count ranged from 1 × 10 9 /L in Clerici et al [ 20 ] to 23 × 10 9 /L in Lévesque et al [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study included a total of 7 case reports, two of them were reported from the United States [ 17 , 18 ], one from Canada [ 19 ], one from Italy [ 20 ], one from Turkey [ 21 ], and one from Greece [ 22 ]. The lowest platelet count ranged from 1 × 10 9 /L in Clerici et al [ 20 ] to 23 × 10 9 /L in Lévesque et al [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ayesh et al reported a case of a 76-year-old female patient who presented with a 5-day history of skin rash, fatigue, mouth pain, visual disturbances, and arthralgia and a preexisting medical history of insulin-dependent T2DM essential hypertension, cerebrovascular accident, and hyperlipidemia. The patient recovered after being diagnosed with secondary ITP associated with COVID-19 [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, non-specific senile purpura is common in older adults, and pathological purpura, including ITP, can be easily misdiagnosed or overlooked in this population 5. The patient was treated with glucocorticoids and intravenous immunoglobulin, as described in the literature 1 6. The patient responded well to the treatment.…”
Section: Descriptionmentioning
confidence: 99%